The Sulima pagoda: east meets west in the restoration of a Nepalese temple - Theophile, Erich; Gutschow, Niels (Orchid Press, 2003)
Literaturverzeichnis Seite 133
"This publication grew out of a symposium organized by the Kathmandu Valley Preservation Trust in November 1999"--Acknowledgements
Keywords: Aufsatzsammlung; Sulima Ratnesvara Temple; Internationale Kooperation; Restaurierung; Tempel; Kathmandutal